Cryptococcus gattii: An Emerging Cause of Fungal Disease in North America - Ashwin Dixit; Scott F. Carroll; Salman T. Qureshi (Interdisciplinary Perspectives on Infectious Diseases)
During the latter half of the twentieth century, fungal pathogens such as Cryptococcus neoformans were increasingly recognized as a significant threat to the health of immune compromised populations throughout the world. Until recently, the closely related species C. gattii was considered to be a low-level endemic pathogen that was confined to tropical regions such as Australia. Since 1999, C. gattii has emerged in the Pacific Northwest region of North America and has been responsible for a large disease epidemic among generally healthy individuals. The changing epidemiology of C. gattii infection is likely to be a consequence of alterations in fungal ecology and biology and illustrates its potential to cause serious human disease. This review summarizes selected biological and clinical aspects of C. gattii that are particularly relevant to the recent North American outbreak and compares these to the Australian and South American experience.